Analisis Dampak Kebijakan Pemerintah Tentang Efektivitas Manajemen Strategi di Perbankan Syariah - febrian, Neyzha Virela Lourencia (Maliki Interdisciplinary Journal, 2025)
s. This research aims to analyze the impact of government policy on the effectiveness of strategic management in Islamic banking. This research uses secondary data from various sources in the form of journals, previous research, books and manuscripts in the National Sharia Finance Committee. The research results show that government policies have a significant influence on the effectiveness of strategic management in the Islamic banking sector in Indonesia, such as policies Law no. 21 of 2008 and various fiscal incentives have provided a solid foundation for the growth and stability of sharia banking. However, in tax-intensive policies there are still challenges that must be overcome, such as tax reductions for deposits and time deposits, tax holidays for new companies, and tax reductions. for sharia commercial banks.